Uma sepultura da Antiguidade tardia em Quintela de Lampaças, Bragança - Queiroga, Francisco M.V. Reimão; Queiroga, Francisco Sá Reimão (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2021)
An archaeological survey carried out in an agricultural field located at Quintela de Lampaças, Bragança, led to the discovery of a Late Antiquity grave. The structure in which the burial is settled is made out of loose stones and clay building materials, and bears a rather unclear configuration that diverges from the known funerary models from this epoch. The dating proposed for the set is the second half of the Vth century AD, as suggested by the materials that are most suitable for dating, such as the pieces of Late Terra Sigillata. Amongst the pile of clay materials that made the covering of the grave was deposited one hammer during the funerary ritual. This hammer is of a known roman type, and is a unique find in the region, in addition to being found in a rather unusual context.